PENGAJARAN MENUJU BUDAYA LITERASI DAN PEMBENTUKAN KARAKTER MUSLIM DENGAN KAJIAN TOKOH UNTUK JURUSAN PENDIDIKAN DASAR (PENDIDIKAN GURU MADRASAH IBTIDAIYAH) - Nuril Mufidah (STAI Ma'had Aly Al-Hikam Malang, 2018)
This study was intended to investigate the process of teaching in the intensive Arabic language at UIN Maulana Malik Ibrahim Malang that designed to foster muslim characters who have the nature and attitude of peace. This began by introducing muslim figures, such as Rosululloh, Ibrahim, Yusuf, Maryam, Hajar, Asiyah and others. Literacy comes from the al Quran and other sources to provide students with knowledge about Islam, peace and strength of faith-based character. Literacy and character growing are important for students as they are in a brilliant and mature phase of thought growth. It is expected that students will direct their thoughts and activities towards the positive and reflect the peace as the spirit of Islam. Results show that the process of learning and teaching begins with reading al Quran and one wise words (mahfudhad) then the lecturer discusses a bit about the verse or mahfudhad by sharing the story of the appropriate moslem character. It usually takes about 30 minutes. Every day students get this literacy review for the first year in campus. Student response to this activity is good. This can be seen from the polite attitude and the tendency towards the peace of new students in this campus; although they differ in the majors or diverse organizations that followed.. This can be seen from the polite attitude and the tendency towards the peace of new students in this campus.